Psychological Distress and Its Mediating Effect on Experiences of Online Risk: The Case for Vulnerable Young People - El-Asam, Aiman; Lane, Rebecca; Katz, Adrienne (Frontiers in Education, 2022)
There is strong evidence showing that vulnerable children and adolescents, such as children who are carers for their family, in care themselves, or who have a physical disability or special educational needs, are at greater risk of mental health problems and poor social wellbeing. Recent research indicates this heterogenous but vulnerable group is also disadvantaged online and may be at greater risk of harm. This study aimed to examine participants’ vulnerability (vulnerable vs. non-vulnerable), psychological distress, parental e-safety support, and online lives, specifically their experiences of online risk. The roles of psychological distress and parental e-safety support were explored as possible mediators and moderators, respectively, for the relationship between vulnerability and online risk. Survey data was collected from 15,278 participants (11–17 years old; M = 12.60, SD = 1.44), 46.6% identified as females, 46.6% identified as males and 6% identified as “other”. Participants were recruited from schools/colleges in different parts of England, of whom 3,242 were categorised as vulnerable. Using Analysis of Variance (ANOVA) the results showed that, when compared to the non-vulnerable participants, the vulnerable groups (single or multiple vulnerabilities) experienced more psychological distress and online risks. They also received less e-safety support from parents or carers. Furthermore, mediation and moderated mediation analysis showed that the relationship between vulnerability and online risk was significantly and partially mediated by psychological distress. Parental e-safety support was found to moderate the relationship between psychological distress and online risk and between vulnerability and online risk. In conclusion, the results demonstrated that vulnerability offline is mirrored online. Psychological interventions and parental e-safety support are required to navigate the internet safely. Children’s services and practitioners should consider online risks in their assessments and interventions.